Investigation of the Discrepancy Between Optically and Gravimetrically Calculated Fiber Volume Fraction in Flax-Fiber-Reinforced Polymer - Maier, Christoph; Beckmann, Alexander; Wittmann, Armin; Koch, Klaus Peter; Fischer, Georg (Journal of Composites Science, 2025)
The fiber volume fraction significantly influences the mechanical properties of fiber-reinforced composites. However, accurate measurements can be particularly challenging in natural-fiber-reinforced polymers. This study compared indirect methods using gravimetric and volumetric measurements with a U-Net-based direct method using micro-CT images for flax-fiber-reinforced polymers made via compression molding at 2.33–13.5 bar. A notable discrepancy was observed between the direct and indirect methods, with the latter yielding a fiber volume fraction approximately 25% lower than what could be determined optically. This difference arose from the matrix being absorbed by the fibers, resulting in a mixed region between dry fiber and pure matrix, further explained using a four-phase model. Our findings indicate that the volume fraction depended on the applied pressure. Specifically, we established a linear relationship between the fiber volume fraction and the pressure up to 9.4 bar, beyond which the fiber volume fraction plateaued. Furthermore, we examined the impact of void distribution in relation to pressure. At lower pressures, voids were distributed irregularly throughout the composite, whereas at higher pressures, the overall number of voids decreased, and they tended to concentrate primarily in the cente
Keywords: natural-fiber-reinforced polymer; fiber volume fraction; convolutional neural network; flax fiber

Measuring Deformation in Natural Fiber-Reinforced Polymer using Mechanoelectrical Effect - Maier, Christoph; Koch, Klaus Peter; Fischer, Georg (IEEE Sensors Letters, 2024)
A conductor embedded in a natural fiber-reinforced polymer is tested for its suitability as a deformation-sensing element in a dynamic three-point bending test with an excitation frequency of 0.1-5 Hz. Research has shown that the peak-to-peak current increases to a frequency of 3 Hz and then remains almost constant, while an increase in the mechanical displacement leads to an exponential increase in the peak-to-peak current. The current signals behave asymmetrically in the entire frequency range investigated when loading and unloading the system. It is currently suspected that contact electrification, which occurs due to conductor detachment or porosity, is the cause of this effect.
CRIS-Team Scopus Importer:2024-07-19
Keywords: Conductors; Contact Electrification; Copper; Current measurement; Deformation sensor; Displacement measurement; Loading; Mechanical variables measurement; Mechanoelectric; Monitoring; Natural Fiber-Reinforced Polymer